2017
DOI: 10.1039/c6ra27329g
|View full text |Cite
|
Sign up to set email alerts
|

Vermicomposting of coal fly ash using epigeic and epi-endogeic earthworm species: nutrient dynamics and metal remediation

Abstract: Study highlights the metal removal efficiency and nutrient dynamics of three potent earthworm species from coal fly ash with a comparative aspect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…The trend of TBG was T2 > T1 > T7 > T6 > T3 > T8 > T4 > T5 > T9. These results show that mixtures composed of 100% by-product give poor results, similar to recent studies, such as Usmani et al [35], who reported that poor biomass growth of earthworms was observed in the treatment comprised solely of coal fly ash, without manure, and Gong et al [36] where better results were obtained when garden wastes were mixed with cattle manure and/or spent mushroom substrate than in solitary. Similar conclusions were obtained during vermicomposting of water lettuce by Suthar et al [37].…”
Section: Biological Resultssupporting
confidence: 88%
“…The trend of TBG was T2 > T1 > T7 > T6 > T3 > T8 > T4 > T5 > T9. These results show that mixtures composed of 100% by-product give poor results, similar to recent studies, such as Usmani et al [35], who reported that poor biomass growth of earthworms was observed in the treatment comprised solely of coal fly ash, without manure, and Gong et al [36] where better results were obtained when garden wastes were mixed with cattle manure and/or spent mushroom substrate than in solitary. Similar conclusions were obtained during vermicomposting of water lettuce by Suthar et al [37].…”
Section: Biological Resultssupporting
confidence: 88%
“…Inclusion of RP to supply 8% phosphorus resulted in 2.81 times more Cr; 2.52 times more Cu; 2.76 times more Cd; 6.3 times more Pb and 3.58 times more Zn; within the earthworm tissues; relative to the control at the end of the experiment. According to Usmani et al. (2017) , the metal accumulation ability in earthworms can be evaluated based on the concentration of the metals within the earthworm tissues divided by the metal concentration in the vermicomposts.…”
Section: Resultsmentioning
confidence: 99%
“…Earthworms have, however, been reported to accumulate heavy metals in their bodies and their involvement in vermicomposting of wastes could reduce the amounts of heavy metals present in the final vermicomposts ( Dai et al., 2004 ; Goswami et al., 2016 ). A protein called metallothionein, which plays a critical role in regulation of heavy metal ion chemistry within cells, has been reported to be produced within the gut of earthworms upon exposure to heavy metals ( Goswami et al., 2016 ; Usmani et al., 2017 ). However, there are no studies that have focused on changes in heavy metals during vermicomposting of rock phosphate, and on influence of the presence of earthworms on heavy metal concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…nitrogen (N) and phosphorous (P), and a lower rate of FA degradation after its application in soil. Moreover, FA has a prevalence of heavy metals in the material and soluble forms 10 . FA comprises a high concentration of toxic heavy metals like Cr, Pb, Cd, Ni, Cu, Zn, etc.…”
Section: Introductionmentioning
confidence: 99%